Treatment of mild domestic wastewater using subsurface constructed wetlands in Malaysia - Saed, Katayon; Zakaria, Fiona; Megat Mohd Noor, Megat Johari; Ghazali, Abdul Halim; Jusoh, Ahmad (Taylor & Francis, 2008)
This study presents the design and performance of pilot scale constructed wetlands in treating a mild domestic wastewater generated from the Faculty of Engineering, Universiti Putra Malaysia. Three cells of subsurface constructed wetlands were built in equal dimensions, two cells were planted with Lepironia articulata, an indigenous Malaysian aquatic plant, while one cell was left unplanted to investigate the role of the plant in treatment process. Those cells were operated at four different hydraulic retention times in two phases ranged from 0.5 to 7 days. The results showed that the constructed wetlands were capable of removing about 56-77% of COD, 50-88% of TSS, 20-88% of TP, 27-96% of NH4+ and 99% of total coliforms numbers. Different hydraulic retention times caused significant effect on removal rate of COD, TP and NH4+, but not to TSS and total coliforms removal. The total number of coliforms was positively correlated with concentration of COD, TP and NH4+ in effluents. Planted wetland cells were superior in both NH4+ and TP removal to unplanted wetland cells.